2021
DOI: 10.2196/32203
|View full text |Cite
|
Sign up to set email alerts
|

Presenting Characteristics, Comorbidities, and Outcomes Among Patients With COVID-19 Hospitalized in Pakistan: Retrospective Observational Study

Abstract: Background COVID-19 became a pandemic rapidly after its emergence in December 2019. It belongs to the coronavirus family of viruses, which have struck a few times before in history. Data based on previous research regarding etiology and epidemiology of other viruses from this family helped played a vital role in formulating prevention and precaution strategies during the initial stages of this pandemic. Data related to COVID-19 in Pakistan were not initially documented on a large scale. In addition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Our study also found that COVID-19 severity is strongly influenced by the presence of multiple comorbidities such that once these comorbidities were controlled in the model, the effects of diabetes, thyroid disorders, mental disorders, and behavioral disorders no longer appeared. These findings suggest that an increase in comorbidities is a significant predictor of COVID-19 severity, ICU admission, ventilator assistance, and even mortality-consistent with previous studies [ 64 , 65 ]. Additionally, multiple comorbidities are typically seen in older individuals.…”
Section: Discussionsupporting
confidence: 91%
“…Our study also found that COVID-19 severity is strongly influenced by the presence of multiple comorbidities such that once these comorbidities were controlled in the model, the effects of diabetes, thyroid disorders, mental disorders, and behavioral disorders no longer appeared. These findings suggest that an increase in comorbidities is a significant predictor of COVID-19 severity, ICU admission, ventilator assistance, and even mortality-consistent with previous studies [ 64 , 65 ]. Additionally, multiple comorbidities are typically seen in older individuals.…”
Section: Discussionsupporting
confidence: 91%
“…[ 15 ] Similarly, Akhtar et al . [ 16 ] have evinced a remarkable association of comorbidities in the escalation of the disease severity. Among comorbidities associated with SARS-CoV-2–linked complications, 39.7% of hypertension, 37.8% of diabetes, 31.2% of asthma, and 11.1% of COPD were spotted.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Pakistan 0.294 b Feb–Aug 2020 Four hospitals in Islamabad-Rawalpindi 1812 Akhtar et al. 26 South Africa 0.166 (0.112–0.228) Based on meta-analysis of 12 studies based in African region 10,756 Li et al. 6 a Mean prevalence and 95% confidence interval provided in parentheses.…”
Section: Methodsmentioning
confidence: 99%